UNIQUENESS IN TRANSLATING ARABIC HAGIOGRAPHY OF SHAIKH ‘ABD AL-QĀDIR AL-JAILĀNĪ: THE CASE OF AN-NŪR AL-BURHĀNĪ - Munip, Abdul (Indonesian Journal of Applied Linguistics, 2018)
In Indonesia, the hagiographical book of Shaikh Ê»Abd al-QaÌ„dir al-JailaÌ„niÌ„ has many versions of translation. One of it is an-NuÌ„r al-burhaÌ„niÌ„, a Javanese translation by Kyai Muslih al-MarÄqiÌ„. Unlike other Javanese translations, an-NuÌ„r al-burhaÌ„niÌ„ is not merely a translation but can be considered a new book, in which the translator added some new information and opinion in it. Therefore, the book is interesting to be investigated deeply to find scientific information about the content of the book, the technique, method, and ideology of translation that are adopted and applied by the translator. Using content analysis, the study finds that the book consists of al-JailaÌ„niÌ„â€™s journey of life, his miracles and teachings. The other findings prove that the translator has implemented various techniques of translation such as calque, borrowing, description, amplification-addition, and adaptation techniques. The translator has tried to make the TT (Target Text) easy to be understood by Javanese people, but he tends to apply literal (linguistic transcodification) method rather than interpretative-communicative (translation of the sense) method. As a result, the TT is still influenced by the structure of Arabic as SL (Source Text) and not natural in everyday use of Javanese language. Thus, it can be inferred that the translator more dominantly adopts the ideology of foreignization than domestication. However, what the translator does is more advanced than the other Javanese translators, who usually use only the word for word or literal translation method. This is the uniqueness in translating al-JailaÌ„niÌ„â€™s hagiography or manaÌ„qib.